The importance and morphobiology of the povlovnia tree - Zakirjan Tojiboyevich Bustonov,; Rakhimov Mansurbek Mavlonjonovich (Universitas Muhammadiyah Sidoarjo, 2019)
It is well known that the findings of scientists in the field of forestry, as well as the introduction of new technologies in production are of great importance. In particular, it is necessary to scientifically substantiate the normal growth and adaptation of new plant species. In addition, the role of trees in the prosperity of every person is unparalleled. This valuable tribute to treasure plays an important role in the economy of the economy, growing and increasing new types of trees and discovering their characteristics. Exemplary exotic trees in cities and villages, qualitative changes in timber supply and research by scientists in this field are clear evidence of the full support of innovation activities under the leadership of the President. Pavlovnia-Pavlovnia is part of the decorative tree species. There are 10 types of plants that are mainly grown in the east. Uzbekistan grows as an ornamental plant. The height of the neck is 12–20 meters, in the fall the normal edges of the leaf are scattered, and the bark opens until the leaf is released. The fruit is a large deciduous worm, the seeds are small, the light is soft. Povlovny made of pepper, roots and seeds.